Personal Voice Assistant: from Inception to Everyday Application - Shazhaev, Ilman; Mikhaylov, Dmitry; Shafeeg, Abdulla; Tularov, Arbi; Shazhaev, Islam (yocto brain, 2023)
The creation of automatic speech recognition systems is a popular trend in the development of information technology. These technologies are developing at a very fast pace, gradually covering more and more areas: already now we can say how firmly they have settled in our lives. The term